Relationship between optical coherence tomography derived intraluminal and intramural criteria and haemodynamic relevance as determined by fractional flow reserve in intermediate coronary stenoses of patients with type 2 diabetes. Issue 10 (30th March 2013) - Reith, Sebastian; Battermann, Simone; Jaskolka, Agnes; Lehmacher, Walter; Hoffmann, Rainer; Marx, Nikolaus; Burgmaier, Mathias
Abstract : Background: The relationship between functional relevance and optical coherence tomography (OCT)-derived measurements of coronary lesions is incompletely understood and of critical importance, particularly in cardiovascular high-risk patients with type 2 diabetes. Objective: To investigate the association between functional relevance of intermediate grade coronary stenoses as assessed by fractional flow reserve (FFR) and OCT-derived lesion parameters in patients with diabetes. Methods: In 46 diabetic patients with stable coronary artery disease, FFR and OCT were performed in 62 coronary lesions with intermediate severity as determined by quantitative coronary angiography. Among lesions haemodynamic relevance was defined as FFR≤0.8. Results: There was a significant association between FFR and OCT-derived minimal lumen area (r 2 =0.379) and minimal lumen diameter (r 2 =0.268), all p<0.001. Receiver operating curve (ROC)-analysis demonstrated an OCT-derived minimal lumen area <1.59 mm 2 and minimal lumen diameter <1.31 mm to be optimal cut-off values to predict FFR≤0.8. Furthermore, in lipid-rich plaques FFR was significantly associated with minimal fibrous cap thickness (FCT, r 2 =0.399). Minimal FCT in lesions with FFR≤0.8 was significantly smaller (60.7±15.0 µm) compared with those lesions with FFR>0.8 (106.0±13.0 µm, p<0.001). ROC-analysis revealed that 0.81 is the ideal FFR cut-off to identify lesions with a minimal FCT≤80 µm (accuracy 97.3%, sensitivity 100%, specificity 93.8%, area under the curve 0.943 (95% CI 0.836 to 1.000)). Conclusions: Haemodynamic relevance of intermediate grade lesions in patients with type 2 diabetes is closely related to (1) intraluminal measurements, which are smaller than previously described in non-diabetic cohorts and to (2) minimal FCT. Furthermore, FFR may be useful to identify vulnerable (minimal FCT≤80 µm) lesions among those with intermediate severity in lipid-rich plaques.